The Antecedents of Carbon Emission Disclosure With Carbon Knowledge as Moderation - Setiawan, Temy; Ahalik, Ahalik; Hakki, Tandry Whittleliang; Novanto, Yosan (DINASTI RESEARCH, 2024)
Climate change is one of the main problems faced by humans in this decade. Several environmental research institutions state that climate change in the next ten years is considered the most threatening long-term risk. Developed countries contribute 65-70% while poor and developing countries contribute the remaining 30%-35%. One of Indonesia's commitments as a country that is a member of the United Nations Framework Convention on Climate Change. The UNFCCC CoP (Climate Change Conference) is an annual world climate conference, where governments meet to discuss plans to address the climate crisis. This will be the 26th meeting. Where this convention is attended by 195 countries that are members of the United Nations (UN). This study aims to analyze the factors that influence the level of carbon emission disclosure, namely to test and analyze: The Influence of Corporate Environmental Awareness, Corporate Carbon Strategy, Green Corporate Business Strategy and Green Supply Chain on Carbon Emission Disclosure. In addition, this study also tests and analyzes the Role of Carbon Knowledge as a moderating variable for the influence of Corporate Environmental Awareness, Corporate Carbon Strategy and Green Supply Chain on Carbon Emission Disclosure. The analytical method used in this study is path analysis with the pattern of relationships between independent variables in this study being correlative and causal. Based on the results of this study, it shows that Environmental Performance has a significant effect on carbon emission disclosure. Carbon management strategy does not have an effect on carbon emission disclosure. Competitive Business Strategy has a significant effect on carbon emission disclosure. And green supply chain management has an effect on carbon emission disclosure. Carbon Knowledge does not strengthen the effect of environmental performance on carbon emission disclosure, Carbon Knowledge does not strengthen the effect of Carbon Management Strategy on carbon emission disclosure. Carbon Knowledge strengthens the effect of Corporate Business Strategy on carbon emission disclosure. Carbon Knowledge strengthens the effect of Green Supply Chain Management on carbon emission disclosure